Genome-wide genetic characterization and selection signatures in Anatolian Merino sheep - T. Karsli (Archives Animal Breeding)
Molecular characterization and identification of selection signals at the genome-wide level facilitate the enhancement of ongoing conservation and selection studies in farm animals. This study aimed to reveal genomic diversity and selection signatures in Anatolian Merino sheep via 351 539 bi-allelic single-nucleotide polymorphisms (SNPs) obtained from the double-digest restriction-site-associated DNA sequencing (ddRADseq) technique. Genetic variability parameters such as minor-allele frequency (MAF), nucleotide diversity (π), observed heterozygosity (HO), and expected heterozygosity (HE) were estimated to be 0.340, 0.235, 0.258, and 0.235, respectively, while the inbreeding coefficient was 0.027 based on runs of homozygosity (ROH). A decreasing trend was detected in the effective population size of Anatolian Merino sheep, the current population of which turned out to be descendants of an ancestral population covering 2500 individuals 400 generations ago. Significant selection signals were detected in 464 SNPs within 14 genomic intervals via the ROH approach, whereas 259 SNPs were categorized into 79 genomic intervals by integrated haplotype score (iHS) statistics. A total of 37 and 72 protein-coding genes overlapped with detected genomic intervals in ROH and iHS approaches, respectively. A survey of a sheep QTL database confirmed that selection signals covered 66 QTL-associated SNPs. A large part of the protein-coding genes under selection pressure were mainly associated with milk production (ROBO1, FSIP2, COBLL1, PTPN12, GSAP, CCDC146, FGL2, FAM185A, FBXL13, LOXL2, R3HCC1, CHMP7, RHOBTB2, PEBP4, SRGAP3, and RAD18) and udder morphology (SYT1, GFPT2, MAPK9, and RASGEF1C), while numerous genes turned out to have effects on total muscle area (PCDH7), bone density (SDK2), carcass traits (MBL2), fecal egg count (LGSN), and immunoglobulin A level in blood circulation (RFXAP, SERTM1, BEND7, PRPF18, FRMD4A, and GRAMD1B). The results of this study confirm that high-density next-generation sequencing (NGS) data could be utilized to characterize local sheep breeds to shape conservation programs and shed light on the past breeding practices of the populations whose phenotypic records are absent.